PENGARUH CUSTOMER EXPERIENCE DAN KEPUASAN PELANGGAN PELANGGAN TERHADAP LOYALITAS PELANGGAN SMARTFREN - Mega Hernawan; Cundo Harimurti (JAMBIS : Jurnal Administrasi Bisnis, 2022)
The purpose of this study was to determine the effect of customer experience and customer satisfaction on customer loyalty to Smartfren. The theory used in this study refers to the opinion of Sheth (Harumi, 2016: 118), which states that,